Influences of Surface Morphology of Nanostructured Rutile TiO2 Nanorods/Nanoflowers as Photoelectrode on the Performance of Dye-sensitized Solar Cell - Bin Ahmad, Mohd Khairul; Murakami, Kenji (UI Scholars Hub, 2013)
Aligned Rutile TiO2 nanorods (r-TNRs) and TiO2 nanoflowers (r-TNFs) were successfully prepared by hydrothermal method. Using hydrochloric acid (HCl) as chelating agent and titanium butoxide (TBOT) as precursor, aligned r-TNRs with r-TNFs were successfully growth onto fluorine-doped tin oxide (FTO) with different morphologies. The influences of surface morphologies to the rutile based Dye-sensitized solar cell (DSC) efficiency are discussed. The highest lightto- electric energy conversion efficiency, 1.80% is achieved using different concentration under simulated solar light illumination of 100 mWcm-2 (1.5 AM).